Kewenangan Bawaslu Dalam Penyelesaian Pelanggaran Administrasi Pemilu - Ririhena, Micael (Bacarita Law Journal, 2024)
Elections are an important element of democracy. The centrality of electoral positions is their ability to distinguish between democratic and non-democratic political systems. It's just that the ideal of realizing a better election until the 5th election in the 2019 Election Reform era has not yet been realized. Various problems and obstacles in the implementation of elections both during the election and before are problems that will certainly have a broad impact if not immediately resolved properly. There are problems in the administration of elections related to dissatisfaction with the decisions of election administrators or criminal or administrative violations that affect the results, which are commonly referred to as election disputes. Disputes in the administration of elections are violations of election administration or dissatisfaction with the decisions of election administrators. Therefore, to cause the election disputes not to interfere with running the constitutional system or government system of a particular country or region, an effective election dispute resolution mechanism is needed and can provide fair decisions for interested parties.